Minimally invasive lateral unicompartmental knee replacement: Early results from an independent center using the Oxford fixed lateral prosthesis - Walker, Tilman; Hariri, Mustafa; Eckert, Johannes A.; Panzram, Benjamin; Reiner, Tobias; Merle, Christian; Gotterbarm, Tobias; Moradi, Babak (The knee, 2020)
Purpose - The aim of the present study was to assess clinical outcome as well as short-term survivorship of fixed-bearing lateral unicompartmental knee replacement (UKR) from a non-designer centre using the Oxford Fixed Lateral prosthesis. - Methods - This single-centre retrospective cohort study reports the short-term results of 51 consecutive patients (52 knees) after fixed-bearing lateral UKR with a minimum follow-up of one year. Survivorship analysis was performed with different endpoints and clinical outcome was measured using the Oxford Knee Score (OKS), objective American Knee Society Score (AKSS-O), range-of-motion (ROM), visual analog scale for pain (VAS), Tegner activity score and UCLA score. - Results - There was no revision surgery, defined as exchange of at least one of the components resulting in a survival rate of 100% at two years. Three patients required further surgical treatment resulting in a survival rate of 94.2% (95% confidence interval (CI): 83.2-98.1%) with the endpoint ‘any reoperation’. Outcome scores, VAS and ROM showed a statistically significant improvement at final follow-up (P<.001). The OKS improved from 26.4±6.9 (12-41) preoperatively to 39.7±8.4 (15-48), the AKSS-O from 54.3±15.3 (18-90) to 82.2±15.6 (40-100), the American Knee Society Functional Score from 56.4±21.3 (10-100) to 83.1±20.2 (five to 100) and the ROM from 123.5±13.5 (90-140) to 134±10.3 (95-150). - Conclusion - Early results of fixed-bearing lateral UKR using the Oxford-Fixed-Lateral prosthesis were encouraging with a significant improvement in pain and knee function as well as an excellent survivorship of 100% at a mean follow-up of two years. Further follow-up is necessary to evaluate the long-term effectiveness of this device and the surgical technique. - Level of Evidence - Level IV, retrospective cohort study.
Gesehen am 09.04.2020